Visitor Preferences for Restorative Landscape Elements in Bogor Urban Parks: A Visitor-Employed Photography Approach - Pamungkas, Aditya Aji; Indah Pratiwi, Prita; Sulistyantara, Bambang (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Human health and well-being are affected by the quality of the environment in which an individual lives. Urban spaces must provide restorative experiences to support public mental health. This study aimed to identify visitor preferences for exciting views and stress-relieving features in urban parks. Using visitor-employed photography to capture direct experiences, the study analyzed geotagged photos to identify landscape views, classified restorative landscape elements, and evaluated their effect on urban park visitors. This research employed spatial analysis of photo distribution using QGIS, photo content analysis using Google Cloud Vision API, and assessment of restorative effect through the Perceived Restorativeness Scale (PRS). The photo-taking hotspots were shaded areas with seating, featuring greenery, sculptures, activities, and landmarks. The results showed 2–3 hotspots with the highest photo density in the three parks. The Cloud Vision API classification results identified that the elements of a restorative landscape can be softscape, hardscape, and other factors. The results of the PRS questionnaire test showed that the three parks had a restorative effect on visitors (< 0.05), Sempur Park had the highest fascination (55.13) and compatibility (55.57) effects, and Heulang Park had the highest coherence effect (56.85) than other parks. These findings emphasize the importance of incorporating shaded seating, greenery, and engaging features into urban park designs to enhance visitor health and well-being.